2014
DOI: 10.3109/09637486.2014.950205
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography LTQ-Orbitrap mass spectrometry method for tomatidine and non-target metabolites quantification in organic and normal tomatoes

Abstract: Tomatoes, members of the Solanaceae plant family, produce biologically active secondary metabolites, including glycoalkaloids and aglycons, which may have both adverse and beneficial biological effects. A new liquid chromatography method that utilized LTQ-Orbitrap MS was developed for the analysis of tomatidine, the main aglycon in tomatoes. Recoveries of tomatidine were >98.3% with the relative standard deviations (RSDs) below 6.1%. The limit of detection (LODs) was 0.0003 mg kg(-1). The limit of quantitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…A related study found that the tomatidine content of 11 analyzed samples was higher in conventional tomatoes than that in organic tomatoes. 29 These results suggest the possibility of future anticancer and anticholesterol studies with selected high-tomatine and high-tomatidine red tomatoes.…”
Section: ■ Introductionmentioning
confidence: 93%
“…A related study found that the tomatidine content of 11 analyzed samples was higher in conventional tomatoes than that in organic tomatoes. 29 These results suggest the possibility of future anticancer and anticholesterol studies with selected high-tomatine and high-tomatidine red tomatoes.…”
Section: ■ Introductionmentioning
confidence: 93%
“…The results imply that the novel polysaccharide might be a candidate for treating gastric cancer. The use of HEG-5 against human gastric cancer is expected to be successful in light of the fact that H. erinaceus mushrooms are reported to prevent gastric ulcers, chronic gastritis, and other digestive tract-related diseases. , …”
Section: Anticarcinogenic Propertiesmentioning
confidence: 99%
“…On the other side, for the identification of unknown compounds, the combination of Fourier Transform Orbitrap MS technology with a linear ion trap MS has been shown to give excellent results as it allowed identification and quantitation in untargeted and targeted analysis (Caprioli, Cahill & James, 2014a;Caprioli, Logrippo, Cahill & James, 2014b). Thus, the first aim of this work was to characterize the unidentified compound in wines with a nominal molecular mass of 176 u (Ginjom et al 2011;Monagas et al 2005) by using two LC-MS platforms, i.e.…”
Section: Introductionmentioning
confidence: 99%